2018
DOI: 10.2478/ers-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Awareness in the Behaviour of Young Consumers - Students of the Faculty of Economic and Technical Sciences of Pope John Paul II State School of Higher Education in Biała Podlaska

Abstract: Summary Subject and purpose of work: The reason for choosing the subject and undertaking the studies were information gaps regarding the behaviour of young consumers in the area of activities related to enviroment. Materials and methods: The study employed purposeful sampling with regards to the participants’ field of study (programmes with environmental education content) and the year of education, as well as stratified sampling according to the structure of the population and its division into groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Herrman's [36] research also showed that the level of education influenced proecological behavior and reflection on what consumers can do for the climate. He backed this up with his research by Łęska and Kuś [40], which stated that students were characterized by a high level of ecological awareness and a sense of responsibility for it, and they are informed and pragmatic consumers. Hence, the following hypothesis can be formulated: H7: higher educated customers better identify 100% biodegradable packaging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Herrman's [36] research also showed that the level of education influenced proecological behavior and reflection on what consumers can do for the climate. He backed this up with his research by Łęska and Kuś [40], which stated that students were characterized by a high level of ecological awareness and a sense of responsibility for it, and they are informed and pragmatic consumers. Hence, the following hypothesis can be formulated: H7: higher educated customers better identify 100% biodegradable packaging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is necessary to intensify the conducted environmental education to educate young consumers about pro-ecological views and to cause consistent behaviour with them (Onwe et al, 2020). Łęska and Kuś (2018) present slightly different results. Their group of respondents is characterised by a high level of environmental awareness and a sense of responsibility for the surrounding environment.…”
Section: Literature Review (And Hypotheses Development)mentioning
confidence: 99%